Emerging therapeutic drug monitoring of anti‐infective agents in Australian hospitals: Availability, performance and barriers to implementation. Issue 2 (31st July 2021) - Sandaradura, Indy; Alffenaar, Jan‐Willem; Cotta, Menino O.; Daveson, Kathryn; Day, Richard O.; Van Hal, Sebastiaan; Lau, Cindy; Marriott, Deborah J. E.; Penm, Jonathan; Roberts, Jason A.; Tabah, Alexis; Williams, Paul; et al.
Abstract : Aims: The purpose of the study was to assess the status of emerging therapeutic drug monitoring (TDM) of anti‐infective agents in Australian hospitals. Methods: A nationwide cross‐sectional survey of all Australian hospitals operating in the public and private health sector was conducted between August and September 2019. The survey consisted of questions regarding institutional TDM practice for anti‐infective agents and clinical vignettes specific to β‐lactam antibiotics. Results: Responses were received from 82 unique institutions, representing all Australian states and territories. All 29 (100%) of principal referral (major) hospitals in Australia participated. Five surveys were partially complete. Only 25% (20/80) of hospitals had TDM testing available on‐site for any of the eight emerging TDM candidates considered: β‐lactam antibiotics, anti‐tuberculous agents, flucytosine, fluoroquinolones, ganciclovir, human immunodeficiency virus (HIV) drugs, linezolid and teicoplanin. A considerable time lag was noted between TDM sampling and reporting of results. With respect to β‐lactam antibiotic TDM, variable indications, pharmacodynamic targets and sampling times were identified. The three greatest barriers to local TDM performance were found to be (1) lack of timely assays/results, (2) lack of institutional‐wide expertise and/or training and (3) lack of guidelines to inform ordering of TDM and interpretation of results. The majority of respondents favoured establishing national TDM guidelines and increasing access to dose prediction software, at rates of 89% and 96%, respectively. Conclusion: Translating emerging TDM evidence into daily clinical practice is slow. Concerted efforts are required to address the barriers identified and facilitate the implementation of standardised practice.